Comparison of sinonasal symptoms in upper respiratory tract infections during the infectious diseases season of November 2023 to March 2024—a cross-sectional study - Straburzyński, Marcin; Romaszko-Wojtowicz, Anna (Frontiers in Medicine, 2024)
Introduction Upper respiratory tract infections (URTIs) are among the most common reasons for patients consulting a general practitioner (GP) during the infectious diseases season, with viruses being the predominant cause. The COVID-19 pandemic has significantly impacted GPs’ perception of these infections. The pandemic’s progression, especially with the emergence of the Omicron variant, has complicated the diagnosis and treatment of URTIs, with evolving symptoms. Aim The aim of this study was to assess the differences in symptoms reported by patients with various infections, such as COVID-19, influenza, common cold, and post-viral rhinosinusitis, during the infectious diseases season of November 2023 to March 2024. Materials and methods The study was conducted in a primary health care clinic, providing care for a population of approximately 10,000 people, among adult patients presenting with URTI symptoms during the 2023/2024 infectious diseases season. Patients qualified for the study were swabbed for SARS-CoV-2, influenza A and B and respiratory syncytial virus (RSV) antigens. Symptoms were assessed with the use of a semi-structured questionnaire. Results Of the 1810 patients presenting with symptoms of URTIs, 276 patients were included in the study. Among patients with COVID-19, symptoms of nasal obstruction (p = 0.005) and nasal discharge (p = 0.001) were less common than in those with influenza or common cold. However, these nasal symptoms were significantly more frequent among patients with COVID-19 who had confirmed previous immunization (COVID-19 history or vaccination) (p = 0.028). Conclusion The incidence of individual sinonasal symptoms varies significantly depending on the aetiological agent of the URTI. This observation may not only help clinicians make the correct diagnosis, but also suggests an inflammatory response in the nasal mucosa and paranasal sinuses that is dependent on the aetiological agent. The study also indicates that this response is altered within the same virus species following immunization. Limitations The study’s limitations include a small sample size (276 patients), focus on one season and one GP practice, and reliance on clinical signs and antigen tests. Nonetheless, the findings provide valuable insights. Further research with larger patient groups and extended follow-up periods is required to confirm these findings.